A new genus and species of inseminating characid fish from the rio Xingu basin (Characiformes: Characidae) - Menezes, Naércio A.; Ferreira, Katiane M.; Netto-Ferreira, André Luiz (Zootaxa, 2009)
Phallobrycon adenacanthus, is described as a new genus and species belonging to Clade A characids of Malabarba & Weitzman (2003). The new taxon is the only characid possessing two developed spines on unbranched portions of fifth, sixth and seventh anal-fin rays associated with intumescent glandular tissue on the anterior portion of the anal fin of sexually mature males. Other non-exclusive diagnostic features of the new genus (observed in male specimens) are: urogenital papilla modified into a copulatory organ, absence of pelvic-fin hooks and glandular tissue not organized into an organ. The presence of these features in members of Clade A and other characids is discussed in order to hypothesize the relationships of Phallobrycon.